Gendering Civil Liberties Under Taliban Theocracy: A Case Of Post-2021 Afghanistan - M V, Sivakumar; Ratha, Subrat Kumar (Jisiera: The Journal of Islamic Studies and International Relations, 2025)
In the aftermath of the US military withdrawal, Afghanistan turned into an Islamic Emirate, installed by the Taliban through harsh interpretation of Sharia laws. Within the framework of the Emirate, this paper intends to ask how the Taliban theocracy excludes women from exercising civil liberties in Afghanistan. Given the context of the gender dimension, the withdrawal of the US military and the re-emergence of the Taliban at the political helm converted Afghanistan into a Theocratic state. They supplied power from the depth of religious sources. Considering the Taliban theocracy as a method of governance, it has been crucial to identify the gender disparities perpetuated through multiple civic restrictions upon women. Unlike modern constitutional democracies, the Islamic Emirates have a distinct interpretation of gender equality, locating the position of women in the political set-up as secondary. With the usage of qualitative and descriptive research methods, this paper examines, along with the question and the emerging grounds, the internal contradictions between the Taliban theocracy and civil liberties in Afghanistan through the perspective of women. Moreover, the paper focuses on assessing the validity of a deep state to legitimise the governance of the Taliban and the exclusion of women from civic life. Having been convinced of the significance of inclusive governance in Afghanistan, this paper also attempts to address the possible political bargain available before the Taliban by allowing women to exercise civil liberty; in return, the Taliban government would produce confidence globally to be recognised as a sovereign state. The findings of this paper encircle the question and the grounds identified and maintain the authenticity by showing the data extracted from both primary and secondary sources with sound analysis.